Role of asymmetrical dimethylarginine in inflammation-induced endothelial dysfunction in human atherosclerosis. - Antoniades, C; Demosthenous, M; Tousoulis, D; Antonopoulos, A; Vlachopoulos, C; Toutouza, M; Marinou, K; Bakogiannis, C; Mavragani, K; Lazaros, G; Koumallos, N; Triantafyllou, C; et al. (2011)
We explored the role of asymmetrical dimethylarginine (ADMA) as a cause of endothelial dysfunction induced by systemic inflammation. In vitro data suggest that ADMA bioavailability is regulated by proinflammatory stimuli, but it is unclear whether ADMA is a link between inflammation and endothelial dysfunction in humans. In study 1 we recruited 351 patients with coronary artery disease (CAD) and 87 healthy controls. In study 2 we recruited 69 CAD, 69 healthy, and 10 patients with rheumatoid arthritis, whereas in study 3, 22 healthy and 70 CAD subjects were randomly assigned to Salmonella typhii vaccination (n=11 healthy and n=60 CAD) or placebo (n=11 healthy and n=10 CAD). Circulating interleukin 6/ADMA and flow-mediated dilation (FMD) were measured at 0 and 8 hours. In study 1, ADMA was inversely correlated with FMD in healthy individuals and CAD patients (P<0.0001 for both). However, interleukin 6 was inversely correlated with FMD (P<0.0001) in healthy subjects but not in CAD patients. The positive correlation between ADMA and interleukin 6 was stronger in healthy (r=0.515; P<0.0001) compared with CAD (r=0.289; P=0.0001) subjects. In study 2, both patients with rheumatoid arthritis and CAD had higher interleukin 6 (P<0.0001) and ADMA (P=0.004) but lower FMD (P=0.001) versus healthy subjects. In study 3, vaccination increased interleukin 6 in healthy (P<0.001) and CAD (P<0.001) subjects. FMD was reduced in healthy subjects (P<0.05), but its reduction in CAD was borderline. Vaccination increased ADMA only in healthy subjects (P<0.001). Systemic, low-grade inflammation leads to increased ADMA that may induce endothelial dysfunction. This study demonstrated that ADMA may be a link between inflammation and endothelial dysfunction in humans.